Sustainable development Goal 16 and the global governance of violence critical reflections on the uncertain future of peace - Donais, Timothy; Edgar, Alistair D. 1962-; Van Houten, Kirsten (Routledge studies in sustainable development, 2024)
"This book brings together a diverse range of scholars and practitioners working at the nexus of peace and development to reflect, at the mid-way point of the Sustainable Development Goals implementation period, what impact Goal 16 has made, or may yet make, towards reducing violence in 'all its forms'. Adopted in 2015, the Sustainable Development Goals include 17 objectives designed to shape and direct the global development agenda through to 2030, with Goal 16 aiming to promote 'peaceful and inclusive societies for sustainable development'. Amidst an ongoing global pandemic, evidence of a fracturing liberal international order, and the persistence of seemingly intractable conflict in large parts of the world, this volume takes stock of current progress towards providing access to justice and ensuring inclusive and democratic institutions. Across 15 chapters, the book's contributors explore the universal aspirations of Goal 16 and its specific implications for conflict-affected states, which continue to experience 'development in reverse', and for historically marginalized groups such as women, youth, the disabled and indigenous peoples. In doing so, it offers a comprehensive assessment of Goal 16's broader contribution to the creation of a more just, peaceful world against the realities of societies emerging from the COVID-19 pandemic and grappling with a deepening climate crisis. This volume will appeal to scholars, researchers, policymakers and postgraduate students in sustainable development, global governance, international relations, global development, international law and political science."